2015
DOI: 10.1152/japplphysiol.00744.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane alleviates muscular dystrophy inmdxmice by activation of Nrf2

Abstract: Sulforaphane (SFN), one of the most important isothiocyanates in the human diet, is known to have chemo-preventive and antioxidant activities in different tissues via activation of nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated induction of antioxidant/phase II enzymes, such as heme oxygenase-1 and NAD(P)H quinone oxidoreductase 1. However, its effects on muscular dystrophy remain unknown. This work was undertaken to evaluate the effects of SFN on Duchenne muscular dystrophy. Four-week-old mdx mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 61 publications
6
61
0
Order By: Relevance
“…Therefore, we suggest that SFN may improve urinary function, not by restraining muscle cell apoptosis, but by preserving muscle function. Similar to other reported studies [29] [40], SFN could improve muscle contractile function, preserve the normal muscle morphology, protect muscles from oxidative damage, and decrease collagen expression. The precise mechanism through which SFN influences the urethral sphincter muscle should be further explored.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we suggest that SFN may improve urinary function, not by restraining muscle cell apoptosis, but by preserving muscle function. Similar to other reported studies [29] [40], SFN could improve muscle contractile function, preserve the normal muscle morphology, protect muscles from oxidative damage, and decrease collagen expression. The precise mechanism through which SFN influences the urethral sphincter muscle should be further explored.…”
Section: Discussionsupporting
confidence: 89%
“…While various studies have demonstrated the promising potential of SFN for the treatment of numerous diseases [28, 29], the present study may be the first to explore the feasibility of SFN for SUI treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Cell lysates were centrifuged at 12,000× g for 20 min at 4°C, and the protein concentrations of the supernatant were determined using the BCA protein assay reagent kit (Thermo) [44-47]. The supernatants containing total protein were then mixed with a corresponding volume of 5× SDS loading buffer and heated at 100°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Nrf2 represents a potential therapeutic target for DMD. Indeed, the induction of Nrf2, by the Nrf2 activator sulforaphane (SFN), was shown to reduce muscle inflammation and fibrosis in dystrophic mice, thereby improving muscle function [74][75][76]. The central role of the Nrf2 pathway in DMD pathophysiology is further supported by clinical studies in which the expression of Nrf2 was found to be upregulated in very young DMD patients early before the appearance of symptoms but not during the progression of disease, when the severity of muscular dystrophy is clearly observed [77].…”
Section: Oxidative Stressmentioning
confidence: 99%